To Evaluate the Effect of Chronic Obstructive Pulmonary Disease on Retinal and Choroidal Thicknesses Measured by Optical Coherence Tomography - Sait Alim; Helin Deniz Demir; Ayşe Yilmaz; Selim Demir; Alper Güneş (Journal of Ophthalmology)
Purpose. To evaluate the retinal and choroidal thicknesses in patients with chronic obstructive pulmonary disease using optical coherence tomography. Methods. The study included 26 patients with chronic obstructive pulmonary disease (COPD) and 26 age-matched healthy control groups. Detailed ocular examinations were performed on all participants. Cirrus EDI-OCT (enhanced depth imaging-optical coherence tomography) was used for choroidal thickness measurements with frame enhancement software. The subfoveal area was used for choroidal thickness measurements. Results. The patients with the chronic obstructive pulmonary disease had an average 239.13 ± 57.77 μm subfoveal choroidal thickness, and the control group had an average 285.02 ± 25 μm subfoveal choroidal thickness. The subfoveal choroidal thickness measurements revealed a statistically significant difference between patients and the control group (p<0.05). There were no statistically significant differences between patients and control group regarding mean macular thickness, central macular thickness, and GCIPL (ganglion cell-inner plexiform layer) thickness. Also, there was no statistically significant difference between patients and control group regarding mean, superior, nasal, inferior, and temporal RNFL (retinal nerve fiber layer) thicknesses. Conclusion. Chronic hypoxemia seems to cause decreased choroidal thickness in patients with chronic obstructive pulmonary disease.